Characterization of mortality in children with sickle cell disease diagnosed through the Newborn Screening Program - Alessandra P. Sabarense; Gabriella O. Lima; Lívia M.L. Silva; Marcos Borato Viana (Brazilian Society of Pediatrics, 2015)
Objective: To characterize the deaths of 193 children with sickle cell disease screened by a neonatal program from 1998 to 2012 and contrast the initial years with the final years. Methods: Deaths were identified by active surveillance of children absent to scheduled appointments in Blood Banks. Clinical and epidemiological data came from death certificates, neonatal screening database, medical records, and family interviews. Results: Between 1998 and 2012, 3,617,919 children were screened and 2,591 had sickle cell disease (1:1,400). There were 193 deaths (7.4%): 153 with SS/Sβ0‐talassemia, 34 SC and 6 Sβ+thalassemia; 76.7% were younger than five years; 78% died in the hospital and 21% at home or in transit. The main causes of death were infection (45%), indeterminate (28%), and acute splenic sequestration (14%). In 46% of death certificates, the term "sickle cell" was not recorded. Seven‐year death rate for children born between 1998 and 2005 was 5.43% versus 5.12% for those born between 2005 and 2012 (p  =  0.72). Medical care was provided to 75% of children; 24% were unassisted. Medical care was provided within 6 hours of symptom onset in only half of the interviewed cases. In 40.5% of cases, death occurred within the first 24 hours. Low family income was recorded in 90% of cases, and illiteracy in 5%. Conclusions: Although comprehensive and effective, neonatal screening for sickle cell disease was not sufficient to significantly reduce mortality in a newborn screening program. Economic and social development and increase of the knowledge on sickle cell disease among health professionals and family are needed to overcome excessive mortality.